The Influence Of Board Members Competency, Public Accountability and Public Policy Transparency on Regional Financial Supervision Community Participation As A Mediation Variable - Bure, Maria Rasdiana; Khuzaini, Khuzaini; Santoso, Bambang Hadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to determine and analyze the effect of Council Member Competence, Public Accountability, Public Policy Transparency and community participation on Regional Financial Supervision at the Sikka Regency DPRD Office. In addition, this study also aims to determine and analyze the influence of community participation in mediating the influence of the Board's Competence on Budgeting, Public Accountability and Public Policy Transparency on Regional Financial Supervision at the Sikka Regency DPRD Office. This type of research is correlational research. In this study, 35 members of the Regional People's Legislative Council of Sikka Regency were sampled. Data were collected through questionnaires and analyzed using descriptive methods and path analysis, namely the sobel test. The results of the descriptive analysis show that the variables of Council Member Competency, Public Accountability, Policy Transparency on Regional Financial Supervision are in good criteria. The results of the path analysis show that: 1) Competency of the Council on Budget has a positive and insignificant effect on Regional Financial Supervision. 2) Public Accountability has a positive and significant effect on Regional Financial Supervision, 3) Public Policy Transparency has a positive and insignificant effect on Regional Financial Supervision, 4) Public Participation is able to mediate the relationship between the Competence of Board Members and Regional Financial Supervision, 5) Public Participation is able to mediate the relationship Public Accountability for Regional Financial Supervision, and 6) Public Participation is able to mediate the relationship between Public Policy Transparency and Regional Financial Supervision.